Investigation of Driving Behavior and Cognitive Ability Concerning Planning Process during Driving of Elderly Drivers - Motoki Shino; Michinobu Nakanishi; Reo Imai; Hiroshi Yoshitake; Yoshio Fujita (International Journal of Automotive Engineering, 2018)
Our research aims to investigate the relation between the driving behavior in the actual environment and the cognitive ability for elderly drivers. To examine the planning process during driving, we analyzed the driving behavior of passing through an intersection with a stop sign and lane changing during driving. As a result of the analysis, about 70% of elderly drivers didn’t drive safely just like driving instructors. Moreover, it was found that elderly drivers of Mild Cognitive Impairment (MCI) group had lower divided attention and alternating attention than that of non-MCI group. The drivers of MCI group were more difficult to decide a task during driving than that of non-MCI group.